2018
DOI: 10.1128/mbio.00415-18
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into Staphylococcus aureus Deep Bone Infections: the Involvement of Osteocytes

Abstract: Periprosthetic joint infection (PJI) is a potentially devastating complication of orthopedic joint replacement surgery. PJI with associated osteomyelitis is particularly problematic and difficult to cure. Whether viable osteocytes, the predominant cell type in mineralized bone tissue, have a role in these infections is not clear, although their involvement might contribute to the difficulty in detecting and clearing PJI. Here, using Staphylococcus aureus, the most common pathogen in PJI, we demonstrate intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
151
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 32 publications
6
151
0
1
Order By: Relevance
“…This was a significant finding, since it is often presumed that periosteum-derived cells are essential for inflammation-induced new bone formation in the long bones (Alexander et al, 2017;Lin et al, 2014). The observations in the ectopic location furthermore indicated that pro-osteogenic effects of killed bacteria cannot be attributed to the specific immune reaction mediated by boneresiding osteoblasts or osteocytes in response to bacteria (Gasper et al, 2002;Yang et al, 2018). The ectopic location lacks the osteogenic and osteoinductive stimuli that are normally present in bone (Albrektsson and Johansson, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This was a significant finding, since it is often presumed that periosteum-derived cells are essential for inflammation-induced new bone formation in the long bones (Alexander et al, 2017;Lin et al, 2014). The observations in the ectopic location furthermore indicated that pro-osteogenic effects of killed bacteria cannot be attributed to the specific immune reaction mediated by boneresiding osteoblasts or osteocytes in response to bacteria (Gasper et al, 2002;Yang et al, 2018). The ectopic location lacks the osteogenic and osteoinductive stimuli that are normally present in bone (Albrektsson and Johansson, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It was also clear from the robust and passionate discussion at the ICM 2018, that the time has come to address the need for a scientifically and clinically functional definitions for: “acute versus chronic” infection (https://www.ors.org/wp-content/uploads/2019/01/Question-1.pdf), “implant colonization versus implant‐related infection” (https://www.ors.org/wp-content/uploads/2019/01/Question-2.pdf), and “persistent wound drainage” (https://www.ors.org/wp-content/uploads/2019/01/Question-3.pdf). These new definitions must incorporate our current understanding that the management of bone and implant‐related infections is inextricably intertwined with the biology of biofilms, infection of osteoblasts and osteocytes, and invasion of the osteocytic‐canalicular network by the bacteria . Thus, the challenge to define treatment protocols is dependent on defining biologic metrics, such as when persister cells become inaccessible to phagocytes, and when antimicrobial levels (and durations) needed to eradicate persister cells are not achievable systemically (minimum biofilm eradication concentration [MBEC]), as discussed by the https://www.ors.org/icm-2018-biofilm-workgroup/ .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, known to survive in osteoblasts and osteocytes (Yang et al . ), SCVs have the potential to persist even when bone is being remodelled and reformed. Three‐dimensional scaffolds which allow bone generation alongside sustained release of antibiotic are under development (Cicuéndez et al .…”
Section: Resultsmentioning
confidence: 99%